Distributed intrusion detection sensor based on optical fiber Mach Zehnder Interferometer - Wong, Desiree Yu Ling. (2010)
A distributed intrusion detection sensor based on an optical fiber Mach Zehnder interferometer (MZI) is proposed and experimentally demonstrated. The MZI technique is employed for distributed sensing with the advantages of simplicity, high sensitivity and high resolution measurements in position. The purpose of this sensor is to detect and locate the exact position of an external disturbance along the entire fiber length. The design of the MZI is such that counter propagating light waves are travelling through the setup simultaneously. A single perturbation was manually induced on the 554.85 m prototype sensor system, illuminated by a coherent DFB laser source. According to fiber optic MZI technique, the time delay due to the phase shift induced by the disturbance is proportional to the output of the MZI. Using signal processing techniques, the location of the disturbance was thus determined by employing cross correlation analysis with the measured time delay of the output sensing signals. From the experimental results, the sensor is capable of measuring both the frequency and location of the perturbation in real time. It has a good frequency response range of 10 Hz to 28 MHz with no distortions in the information of the received perturbation. The sensing system also has good repeatability in the output sensing signals results and has a high positional resolution of 47.5 m. Hence, this proposed optical fiber MZI configuration for the distributed intrusion detection sensor has a good potential in future applications of detecting multiple intrusions and their respective frequencies.